The EU design approach : a global appraisal - Kur, Annette, 1950-; Levin, Marianne, 1942-; Schovsbo, Jens (Edward Elgar Publishing, 2018)
EU legislation for the protection of designs has been described as a 'third way' in contrast to traditional concepts of design protection. This book provides a thorough appraisal of the EU's unique Design Approach; assessing its formation, development and impact over the past decade. The EU Design Approach explores the rationale behind the creation of the Approach; including contributions from two leading EU scholars who were involved in its conception. The contributing authors provide an assessment of the impact that the Design Approach has had on present EU laws, national law systems and adjacent areas of law including copyright and competition law. Chapters also explore more problematic issues associated with the Approach such as: the role of design law in the wider EU framework for the protection of product shapes, and the balancing of interests between rights holders and users. Overall, this book demonstrates that the Design Approach has been largely successful in its aims despite there being some ongoing points of contention. IP scholars will find this book to be a valuable resource of historical and comparative analysis. Practicing IP lawyers and policy makers will also benefit from the inclusion of up-to-date EU and national case law.